2017
DOI: 10.1007/s00405-017-4674-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of risk factors influencing the outcome of the Epley maneuver

Abstract: Benign paroxysmal positional vertigo (BPPV) is the most frequent type of vertigo. The treatment of canalithiasis of the posterior semicircular canal consists in performing a particle-repositioning maneuver, such as the Epley maneuver (EM). However, the EM is not effective in all cases. The objective of this study is to identify risk factors, which predict the EM failure, among the clinical variables recorded in anamnesis and patient examination. This is an observational prospective multicentric study. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Of the six articles without numeric age‐group data, five studies found no influence of age on treatment outcome after one CRP 24,29,37,42,61 . Korres et al 51 found a better initial response to treatment in the younger age group ( p < 0.001) 51 …”
Section: Resultsmentioning
confidence: 98%
“…Of the six articles without numeric age‐group data, five studies found no influence of age on treatment outcome after one CRP 24,29,37,42,61 . Korres et al 51 found a better initial response to treatment in the younger age group ( p < 0.001) 51 …”
Section: Resultsmentioning
confidence: 98%
“…However, other studies have shown a negative correlation between osteoporosis/vitamin D deficiency and BPPV (9). Other studies investigating the role of other prognostic factors, such as arteriosclerotic turn over (10), prior trauma or labyrinthitis (11), previous BPPV history, and intensity of nystagmus (12) predicted a low correlation for BPPV outcomes. Furthermore, abnormal vestibular evoked myogenic potentials (VEMPs), as neurophysiological parameters, showed a chronic and resistive BPPV prognosis (13), while vertigo occurring immediately after a maneuver as a liberator sign, correlated with the success of treatment (14).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported associations between hyperlipidemia and PV [18-20]. Hyperlipidemia can cause vascular damage to the inner ear [21,22].…”
Section: Discussionmentioning
confidence: 99%